Pustakawan akademik sebagai mitra riset di perguruan tinggi - Ulpah Andayani (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2016)
This paper deals with the role of academic librarians in higher education program. The focus ofthe study is to explain the roles of academic librarians as research partner in the higher educationprograms. Based on the analysis of the literatures, it was found that academic librarians have astrategic role in successing the research program. There are three main roles of academic librariansin the research activities, that are providing information research services, conducting research skillstraining, and assisting academic members in publishing and disseminating the research findings.Furthermore, the Librarians serve and assist the researchers individually in performing the researchactivities, as well as arrange and implement programs in groups or classes program in teachingresearch skills through information literacy program. Through the teaching of information literacy,the academicians are provided the ability to identify the sources of information, the ability to searchinformation, and the ability to manage the citations.